C-reactive protein as a potential biomarker in psychiatric practice: Are we there yet? - BAYSAK, ERENSU; ARICIOĞLU, FEYZA (TAYLOR & FRANCIS LTD, 2022)
Objectives Serum or plasma levels of C-reactive protein (CRP) and high-sensitivity CRP (hsCRP) are widely used clinical markers of inflammation in other branches of medicine, whereas its clinical use in psychiatry has been limited to research studies. We aimed to assess the possibility of using CRP/hsCRP in psychiatric practice. This is a review and evaluation of various lines of evidence supporting the concept of CRP as a biomarker for psychiatric disorders in certain conditions. Methods We searched the literature for studies which assessed CRP/hsCRP levels in various psychiatric disorders. Results The accumulating evidence from large studies and meta-analyses allows us to understand the role of CRP in major psychiatric disorders and increase our understanding of specific symptoms and subtypes of disorders. CRP may be considered a 'psychiatric biomarker' which can alert clinicians about neuroinflammation, adverse effects of medications, cardiometabolic status, co-morbidities, and may also predict clinical outcomes and guide optimal treatment.selection. Conclusion Although the underlying pathophysiological role of CRP and hsCRP is still elusive and the association between CRP and psychiatric disorders is inconsistent, CRP holds promise to become a psychiatric biomarker.
Keywords: C-reactive protein; CRP; hsCRP; neuroinflammation; psychiatry; POSTTRAUMATIC-STRESS-DISORDER; ALL-CAUSE MORTALITY; INFLAMMATORY MARKERS; BIPOLAR DISORDER; HS-CRP; ANTIDEPRESSANT TREATMENT; CARDIOVASCULAR-DISEASE; DEPRESSION TREATMENT; TREATMENT RESPONSE; ASSOCIATION